Three week hypergravity training intervention decreases ground contact time during repeated jumping and improves sprinting and shuttle running performance - Scudamore, E. M.; Lowe, J. B.; Pribyslavska, V.; Johnson, S. L.; Stevenson, M. C.; Langford, T. W.; Green, J. M.; O'Neal, E. K. (International Journal of Exercise Science, 2016)
This study examined the effects of a non-traditional training method, hypergravity training (HT), on anaerobic performance. Highly active men (n = 9) completed a 3 week HT protocol in which weighted vests were worn 8 h/day, 4+ days/week separate from training. Vest loads were 11.2 ± 0.6% of body mass during week one, and increased to 13.2 ± 0.7% (week 2), and 16.1 ± 0.4% (week 3). Performance testing included power clean 1-RM (PC), counter movement jumps, 4 continuous jumps, 36.6 m sprints (SP), a 137.2 m short shuttle run (SSR), and a 274.3 m long shuttle run (LSR). A 3 week non-hypergravity training period (NHT) proceeded HT. Baseline SP improved from 4.69 ± 0.29 s to 4.58 ± 0.22 s post-treatment, and regressed after NHT (4.69 ± 0.24 s) (p = 0.006, ES = 1.80). Improvements in SSR (p = 0.012, ES = 1.71) occurred from baseline (26.7 ± 1.5 s) to post-treatment (26.2 ± 1.4 s), followed by a return to near-baseline values (26.9 ± 1.8 s). Jumping tasks displayed similar trends, but no statistical differences and modest effect sizes (0.51 - 0.62) were found except for improved ground contact time during repeated jumps post-HT (ES = 2.26). PC and LSR performances did not improve. Three weeks of HT significantly enhanced short running task performances and decreased ground contact time between 4 continuous jumps. HT may be incorporated into training programs prior to key points in an athletic season without hindering the quality of regular training session activities